Antibiotic therapy of upper respiratory tract and ENT infections in children - V. A. Bulgakova; L. R. Selimzyanova; T. E. Privalova; E. N. Kareva (Лечащий Врач)
Background.In the outpatient setting, it is important for pediatricians and general practitioners to determine the indications and empirically prescribe an effective antibacterial drug in a timely manner. In the Russian Federation in recent years, clinical guidelines for various diseases have been developed and approved, defining indications for systemic antibacterial therapy, according to which amoxicillin is the starting drug for most bacterial acute respiratory infections, and inhibitor-protected aminopenicillins (amoxicillin/clavulanate) are recommended in case of ineffective therapy or drug-resistant pathogens.Conclusion. The article presents the determining indications for the prescription of antibacterial therapy and the peculiarities of the choice of the starting antibacterial drug in such infectious-inflammatory diseases of the upper respiratory tract in children as acute tonsillitis and/or pharyngitis, acute sinusitis, acute otitis media. It is shown that the most optimal dosage form for the use of antibacterial drugs is dispersible tablets, which increases the safety of treatment and patient adherence to medical recommendations.